The Effect of Credit Interest Rates, Digital Marketing, and Social Influence on Millennial Generation's Interest in Adopting Online Loan Services (Peer to Peer Lending) - Nita Safitri, Zara; Restuningdiah, Nurika; Makaryanawati, Makaryanawati (Lafadz Jaya Publisher, 2023)
Current technological developments have made financial services, initially confined to conventional systems, now use more financial technology services. Fintech products are usually a system built to carry out specific financial transaction mechanisms, one of which is online lending (peer-to-peer lending). Some people choose to use peer-to-peer lending without looking at the credit interest rate and without first checking if the company is registered with the OJK or not. As a result, many default risks occur due to mistakes in analyzing peer-to-peer lending loans. As well as several fintech applications still need to be officially registered with the Financial Services Authority, resulting in people experiencing the risk of default with large loan interest. The purpose of this research is to discover the factors that influence the behavioral interest of the millennial generation in adopting online loan services. The research method used is convenient random sampling, with a total sample of 70 respondents. The results of this study show that digital marketing and social influence variables positively affect the millennial generation's interest in adopting online loan services. Meanwhile, loan interest rates have a negative impact because the lower the interest rate is given, the more people will use online loan services. The results of this study show that digital marketing and social influence variables positively affect the millennial generation's interest in adopting online loan services. Meanwhile, loan interest rates have a negative impact because the lower the interest rate is given, the more people will use online loan services. The results of this study show that digital marketing and social influence variables positively affect the millennial generation's interest in adopting online loan services. Meanwhile, loan interest rates have a negative impact because the lower the interest rate is given, the more people will use online loan services.